IMPLEMENTASI ASAS PERADILAN SEDERHANA, CEPAT DAN BIAYA RINGAN DALAM PERKARA PERCERAIAN PADA MASA PANDEMI COVID-19 DI PENGADILAN AGAMA SUNGGUMINASA - Ayu Ashari; Halim Talli; Muhammad Fajri (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
This research discusses the implementation of simple, fast and low-cost justice principles in divorce cases during the Covid-19 pandemic. The outbreak of the Covid-19 pandemic has not only had an impact on community activities in general, but the Religious Courts as an institution have also experienced several obstacles in resolving cases, especially with the increase in divorce cases. Therefore, in the end, the author explored how effective the application of the principle of simple justice was, fast and low cost, especially in divorce cases during the Covid-19 pandemic at the Sungguminasa Religious Court. The type of research used is empirical legal research, namely a study with field data as the main data source such as the results of interviews. The results of this study reveal that the effectiveness of applying the principle of simple, fast and low-cost justice in divorce cases during the Covid-19 pandemic at the Sungguminasa Religious Court was not effective, due to several factors, namely from the court, the litigants, both the plaintiff/defendant and witness, in terms of the ineffectiveness of the application of this principle, it can be measured from the presence of several cases which were not decided on time, in this case beyond the allotted time, namely more than 5 (five) months since the case was registered.